Geological development of Heard Island, Central Kerguelen Plateau. Issue 1 (2nd January 2016) - Duncan, R. A.; Quilty, P. G.; Barling, J.; Fox, J. M.
ABSTRACT: We report 40 Ar– 39 Ar laser step-heating age determinations on 15 stratigraphically controlled lava flows and intrusive rocks from Heard Island, Central Kerguelen Plateau (Indian Ocean). The island history began with uplift of pelagic limestone intruded by 22 Ma gabbro sills. Subaerial and wave erosion levelled the early island, producing an unconformity onto which pillow lavas, tuffaceous sediments and shallow-water, fossiliferous marine siltstone (Drygalski Formation) were deposited, beginning in late Miocene time. Two volcanic systems then formed in the late Quaternary. Big Ben dominates the larger southeast part of the island, while Mount Dixon occupies the northwest Laurens Peninsula. Feeder dykes and the early lava flows in both systems are 400–200 ka. Lava flows with evolved compositions (trachytes, trachyandesites) erupted 100–20 ka. Well-preserved parasitic cones exposed at low elevations are 15–10 ka and younger. Mawson Peak, near the summit of Big Ben, has erupted lava flows as recently as 2007. Heard Island, and nearby active McDonald Island, are subaerial features of a larger Neogene volcanic region of Central Kerguelen Plateau that includes several large sea knolls and recently identified submarine fields of small cones. This broadly distributed volcanic activity is linked to incubation of plume material at the base of the nearly stationary overlying Central Kerguelen Plateau.